Evaluation of Kappa Index as a Tool in the Diagnosis of Multiple Sclerosis: Implementation in Routine Screening Procedure - Sanz Diaz, Carmen Teresa; de las Heras Flórez, Silvia; Carretero Perez, Mercedes; Hernández Pérez, Miguel Ángel; Martín García, Vicente (Frontiers in Neurology, 2021)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system. Previous studies have shown that cerebrospinal fluid Kappa-free light chains (Κ-FLC) may have a role in MS diagnosis. In this regard, the Kappa Index (K-Index) has demonstrated higher sensitivity and slightly lower specificity than oligoclonal bands (OCB), the gold standard, for the detection of intrathecal immunoglobulin synthesis, a feature of MS. Here, we have evaluated the performance of the K-Index (K-Index= CSF/serum Κ-FLC divided by CSF/serum albumin) for the differential diagnosis of MS in a cohort of patients with suspected MS. Kappa-free light chains were quantitatively measured in parallel serum and CSF samples by turbidimetry (Freelite Mx reagent on an Optilite system, The Binding Site Group Ltd). From the 160 (63.4%) of the total of 252 patients who had Κ-FLC in CSF <0.03 mg/dL, below the sensitivity limit of the technique, only one had a diagnosis of MS. However, the absence of OCB in this same patient suggested no synthesis of intrathecal immunoglobulin. Globally, MS patients presented significantly higher K-Index levels when compared to patients without a MS diagnosis (66.96 versus 0.025, respectively. P<0.0001). In agreement, patients with positive OCB testing also exhibited higher K-Index levels than patients negative for OCB (65.02 vs 0.024, respectively. P<0.0001). An optimal K-Index cut-off of 3.045 was defined by ROC analysis for screening suspected MS, achieving a higher diagnostic sensitivity and slightly lower specificity than OCB (Sens.: 0.9778 and Spec.: 0.8629, vs Sens.:0.8889 and Spec.: 0.9086, respectively). A previously reported K-Index cut-off of 6.6 also shown good diagnostic performance (Sens: 0.9333; Spec.: 0.8731), validating its power as a diagnostic biomarker for MS. Finally, a time and cost effective algorithm for MS screening was proposed that would offer an initial rapid evaluation of the intrathecal immunoglobulin synthesis through the Κ-FLC in CSF and K-Index analysis, followed by reflexing OCB testing, that may be ordered more selectively.